2004
DOI: 10.1063/1.1644611
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel conductivity and conductance switching in supramolecular structures of an organic molecule

Abstract: We have demonstrated conductance switching between multilevel states in devices based on Rose Bengal molecules embedded in supramolecular matrices. Two mechanisms, namely electroreduction and conformational change of the molecules, resulting in conjugation modification have been proposed to be applicable in these devices. In a low voltage region, reverse-bias induced electroreduction of Rose Bengal facilitated conjugation restoration in the backbone of the molecule and, hence, switching to a high-conducting st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 16 publications
2
75
1
1
Order By: Relevance
“…1͒ have been shown to switch resistively with high R off / R on values ͑with R off resistance in the high resistive state and R on resistance in the low resistive state͒, [12][13][14][15][16] but the switching mechanism is still under discussion. Possible explanations are a change in the electrical conjugation of the rose bengal molecule by electrochemical reduction, 14 a twist of the upper benzene ring, 12 and the formation and breaking of metallic filaments. Similarly, some changes in the electrodes ͑e.g., by oxidation͒ or the interface between the electrode and the molecular film can cause the resistive switching.…”
Section: Introductionmentioning
confidence: 99%
“…1͒ have been shown to switch resistively with high R off / R on values ͑with R off resistance in the high resistive state and R on resistance in the low resistive state͒, [12][13][14][15][16] but the switching mechanism is still under discussion. Possible explanations are a change in the electrical conjugation of the rose bengal molecule by electrochemical reduction, 14 a twist of the upper benzene ring, 12 and the formation and breaking of metallic filaments. Similarly, some changes in the electrodes ͑e.g., by oxidation͒ or the interface between the electrode and the molecular film can cause the resistive switching.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, considerable attention has been directed toward electrical switching and memory devices which consist of organic materials, polymers and charge transfer complexes with an electrical bistable function [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Memory devices based on organic (polymer) materials have many advantages compared to inorganic memory devices, such as flexibility, simple processing, a low cost, and largearea fabrication via printing technology.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions include a lower threshold voltage (<5 V), a higher ON/OFF ratio (>orders of 103), a rapid switching time (<100 ns), longer retention (>10 years at 60 o C), higher duration (>106 cycles) and a high memory capacity (>109 bite). Among the several types of organic (polymer) memory devices, such as trapping filling [13], filamentary conduction [14,15], electrochromicity [16], electroreduction and conformation changes of molecules [17,18], organic/metal/organic (O/M/O) structures [19][20][21][22] and charge transfer (CT) complex [23][24][25][26][27][28][29][30][31], last two organic (polymer) memory devices, organic/metal/organic (O/M/ O) structures and charge transfer (CT) complex, are entitled to be used for practical application. Especially, organic (polymer) memory devices based on the CT complex are expected to show fastest switching times (<10 ns), as the switching takes place via a rapid electronic process (redox reaction) rather than a slow process (chemical reaction, a conformational change, or isomerization), as reported in other memory devices.…”
Section: Introductionmentioning
confidence: 99%
“…Bandyopadhyay et al [84] found multilevel conductance switching in supramolecular structures of Rose Bengal molecules, the mechanism of which was attributed to a combination of electrochemistry and conformation change in Rose Bengal molecules. Field-induced conformation change has also been adopted by various researchers to explain the multilevel effect [85], while still other researchers attributed the multilevel effect of their devices to a filamentary mechanism [77,83].…”
Section: Multilevel Effect Of Two-terminal Organic Memory Devicesmentioning
confidence: 99%